Tribological behavior of WC-4.32MgO-3.68B2O3 composite. Issue 1 (August 2021) - Lai, Jiaming; Li, Jingmao; Zhu, Dezhi; Liang, Liang; Qu, Shengguan; Li, Huiyun; Li, Xiaoqiang
Abstract: WC-4.32MgO-3.68B2 O3 composite material was prepared by S park plasma sintering technology, and then Si3 N4 ball was used as the counter-grinding material to study the friction and wear behavior under different loading conditions by means of fretting friction. The research results show that: the distribution of the second phase has a significant effect on the wear behavior of the composites. During the fretting friction process, second phase particles peeled off from the structure, causing the abrasion of the matrix to increase. The research found that with gradually increase of the load, the friction coefficient of the material gradually decreases, but the degree of wear gradually increases. The number of furrows also increased significantly, which was related to the wear degree of convex on the surface of the materials. It can be observed from the wear scar that the main wear mechanisms of composite materials are abrasive wear and oxidative wear.